Assessment of the availability of infrastructure, manpower, materials and knowledge of health care providers regarding child health care services in the sub centers of a block of Dibrugarh district, Assam - Paul, Debarshi; Gogoi, Gourangie; Baruah, Rupali (International Journal Of Community Medicine And Public Health, 2019)
Background: The SCs are under constant criticism for their inability to deliver quality services. Every year some 12 million children of developing countries die before they reach their fifth birthday. Around 90% of mortality rate can be prevented by the improvement of health care quality. Methods: Cross-sectional study conducted among health care providers of sub-centers in a randomly selected block of Dibrugarh district of Assam. Results: All SCs had two health worker (female)/ANMs and a multipurpose health worker male (MPW Male). Only 20% SCs adhered to scheduled opening but 100% adhered to scheduled closing time of the health facilities. 100% of SCs were housed in government building. 70% of the SCs had motorable roads. All the SCs had a regular and good supply of BCG, OPV, measles, TT, pentavalent (90% SCs) vaccines. Conclusions: SCs play a crucial role to decrease the morbidity and mortality of under five children in the rural areas. Full-fledged SCs with sufficient manpower, good infrastructure and good knowledge of delivery of child health care among health care providers would definitely improve the level of child health care provided to the community.